Incidence of Common Risk Factors in Patients with Utero Vaginal Prolapse - Nisar, Mehreen; Nisar, Bushra; Nisar, Aqsa (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
ABSTRACT BACKGROUND:- To determine the frequency of common risk factors in patients with utero vaginal prolapse at Obstetric and Gynecology department, Khyber Teaching Hospital, Peshawar METHODS: This study was conducted at Obstetric and Gynecology department, Khyber Teaching Hospital, Peshawar. Duration of study was 6 months (11th February 2011to 11th August 2011) in which a total sample size was 211 patients calculated from 6.8% risk of utero vaginal prolapsed after two or more vaginal deliveries, 95% confidence interval with 3,4% margin of error under WHO software for sample size determination was taken. More over it was a cross sectional (descriptive) study in which consecutive (non probability) sampling technique was used. RESULTS: In this study most of the patients 58% were in age range 51-60 years followed by 35% patients were in age range 41-50 years and 7% patients were in age range 30-40 years. Mean age was 52 years with standard deviation ± 1.26. Common risk factors of uterovaginal prolapsed among 211 patients was analyzed. incidence of Utero vaginal prolapse was mostly found (48%) in those patients who had deliveries assisted by unskilled birth attendant followed by 40% patients who had multiple vaginal deliveries, 33% patients who were grand multi parous and 7% patients who had chronic constipation. CONCLUSION: Our data confirmed that advanced age ,low availability of skilled birth attendant, increasing number of vaginal births , increasing parity are associated with statistically significant trend toward increased pelvic organ prolapse. Finally information compaigns, preventive care management and early treatment of genital prolapse should be initiated to reduce this public health problem KEY WORDS: Parity, Pelvic Organ Prolapse, Uterovaginal prolapse,